Case Report: Combined CDK4/6 and MEK Inhibition in Refractory CDKN2A and NRAS Mutant Melanoma - Forschner, Andrea; Sinnberg, Tobias; Mroz, Gabi; Schroeder, Christopher; Reinert, Christian Philipp; Gatidis, Sergios; Bitzer, Michael; Eigentler, Thomas; Garbe, Claus; Niessner, Heike; Röcken, Martin; Roggia, Cristiana; et al. (Frontiers in Oncology, 2021)
There are only limited treatment options for metastatic NRAS mutant melanoma patients with resistance to immune checkpoint inhibitors. Besides activation of the mitogen-activated protein (MAP) kinase pathway, they often have additional disturbances in cell cycle regulation. In contrast to BRAF mutant melanoma, no targeted therapy has been approved for NRAS mutant melanoma so far. Here we present a NRAS mutant melanoma patient with response to combined binimetinib and ribociclib therapy after having characterized the molecular defects of the tumor by panel sequencing. Next generation sequencing (708 cancer genes) of a soft tissue metastasis revealed a homozygous deletion of CDKN2A in addition to the known NRAS mutation, furthermore amplification of CCNE1 and CDK6. Immunohistochemical staining of the altered cell cycle genes confirmed loss of p16, reduced expression of p21, as well as high expression of CDK6 and Cyclin D1. As the patient had been progressive under combined immunotherapy, according to the recommendation of the molecular tumor board, targeted therapy with combined MEK and CDK4/6 inhibition was initiated. Treatment response was monitored with PET/CT and liquid biopsy, serum LDH and S100. In addition, a patient-derived xenograft (PDX) was used to prove the efficacy of both drugs in combination. Moreover, senescence-associated beta-galactosidase staining showed that more cells were senescent with the combination treatment of binimetinib and ribociclib. Our case demonstrates how an individual, molecular-based therapeutic approach could be found based on next-generation sequencing results. Furthermore our report shows the fruitful and efficient cooperation of dermatooncologists, human geneticists, molecular pathologists, biochemists, radiologists and nuclear physicians. Further studies are urgently needed to expand the very limited therapeutic landscape of NRAS mutated melanoma.